The impact of online classes on students' learning behavior during COVID-19 - Ismael, Farraniva; Sultan, Asnora; Sangcopan, Hamidah (Journal of English and Education (JEE), 2025)
The COVID-19 pandemic has posed significant global challenges, adversely affecting various aspects of human life, including education. This study aimed to analyze students' problematic behaviors in the new learning modality to mitigate the risks of academic failure. Specifically, it examined the impact of online classes on the learning behaviors of 100 students during the COVID-19 pandemic. In the first semester of the academic year 2022–2023, the study employed a mixed-methods approach, combining qualitative and quantitative research. The researchers disseminated a questionnaire based on Nouri (2021) and interviewed ten respondents to gain deeper insights. The findings revealed that the pandemic had an unexpected and profound impact on students' ability to adapt to new educational modes, compounded by financial difficulties and technological demands. The study underscored critical areas for educators to address to promote effective learning. Notably, the qualitative data highlighted that some students faced significant challenges due to extremely slow internet speeds in their areas, which severely hindered their engagement with online learning. The originality of this study lies in its focus on academic institutions during a critical period, providing insights into how pandemic-induced disruptions shaped the educational experience. This offers valuable implications for educators, policymakers, and institutions to enhance remote learning strategies and support students in future educational crises.